The Influence of Scarcity Promotion, Electronic Word of Mouth, and Promotional Appeal on Impulsive Buying Behavior of E-Commerce Application Users - Kushariyadi Kushariyadi; Muhammad Hery Santoso; Megawati Beddu; Vivid Violin; Ratu Nadya Wahyuningratna; Iwan Henri Kusnadi (Institute of Advanced Knowledge and Science, 2026)
This research intends to examine the effect of Scarcity Promotion, Electronic Word of Mouth and Promotional Appeal on Impulsive Buying Behavior of e-commerce application users. The research used a quantitative approach utilizing the survey method of 220 e-commerce application users who were recruited using a purposive sample strategy. Data were acquired using online surveys and analyzed using multiple linear regression. Prior to the hypothesis testing, the data were examined using validity and reliability tests and the classical assumption test. The findings demonstrated that Scarcity Promotion, Electronic Word of Mouth, and Promotional Appeal had a good and substantial effect on Impulsive Buying Behavior partly and concurrently. The study results revealed that perceived scarcity, effect of digital reviews and promotional attractiveness were key determinants of impulsive purchase behavior among the e-commerce application users. This research contributes theoretically to the development of consumer behavior and digital marketing literature. It also has practical implications for e-commerce enterprises to build more successful promotional methods.